PERSEPSI ANAK TERHADAP POLA ASUH DI PANTI ASUHAN AL-HIDAYAH KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - ', T. Juliana; Erlinda, Sri; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by several of the children who found their caregivers who imposed the will to them so that they have a negative judgment to their caregiver, There are some children who think that their caregivers are less concerned about ther interests of foster children so that they feel neglected by caregivers, Then, if there are they are in foster care in some children did a mistake and broke the rules, they will get sanction such as cutting their allowance that it makes the child feel that their caregivers. Because of the small number of caregivers in this orphanage is causing, some didn’t care about the children feel less attention, so the emergence of some perception of children to caregivers. The purpose of this study was to determine the same perception Against Children in Orphanages Parenting Al-Hidayah Payung Sekaki Pekanbaru. The population in this study were all foster children Orphanage Al-Hidayah Payung Sekaki Pekanbaru which consist of 26 people. The Data collection is a questionnaire for foster children that consists of 18 questions and a structured interview for caregivers in order to strengthen the questionnaire answers to questions. Qualitative analysis of data with through percentage. From the calculation of the percentage of respondents overall earned Very Good answer as much as 77.38% are in the range of 75, 01% - 100%. Thus the hypothesis that perception of Children Against Parenting otherwise lacking in both the Orphanage Al-Hidayah Payung Sekaki Pekanbaru in decline. Based on the research results, it can be stated that the perception Against Children in Orphanages Parenting Al-Hidayah Payung Sekaki Pekanbaru is very good.Key Words : Perception, The Parenting